Positive electrode active material

By introducing the second oxide component into the lithium positive electrode active material to form secondary particles with improved cycle stability, the problem of insufficient cycle stability of existing materials at room temperature and elevated temperature is solved, and longer battery life and higher performance efficiency are achieved.

CN119562932APending Publication Date: 2025-03-04TOPSOE BATTERY MATERIALS AS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380049407.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-07-07
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing lithium positive electrode active materials have insufficient cycling stability at room temperature and elevated temperatures, which affects the long life and efficient performance of the battery.

Method used

Using a positive electrode active material containing lithium transition metal oxide spinel particles and a specific oxide component, secondary particles with improved cycle stability are formed by providing a second oxide component on the surface of the particles or dispersing the second oxide component at the interface between the single crystal particles.

Benefits of technology

The cycle stability of lithium positive electrode active materials at room temperature and elevated temperature is significantly improved, extending the service life of the battery and improving its efficient performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562932A_ABST
    Figure CN119562932A_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material comprising: (a) a first component comprising lithium transition metal oxide spinel particles; (b) a second oxide component selected from oxides of Sr, Y, Zr, Nb, La and W and mixtures thereof; wherein the positive electrode active material is: (i) one or more single crystal particles comprising a first component wherein the arithmetic mean value of the minimum Feret diameter of the particles measured using a scanning electron microscope is not greater than 3 [mu] m wherein a second oxide component is at least partially disposed on the surface of the particles; and / or (ii) secondary particles comprising agglomerated single crystal particles of the first component wherein the second oxide component is dispersed on the surface of the single crystal particles at the interface between the single crystal particles, thereby spreading throughout the secondary particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode active material and a preparation method thereof. Background Art

[0002] The development of rechargeable battery materials with high energy density has become a major research topic due to their wide applications in electric vehicles, portable electronic devices, and grid-scale energy storage. Since their first commercialization in the early 1990s, lithium-ion batteries (LIBs) have offered many advantages over other commercial battery technologies. In particular, their high specific energy and specific power make LIBs the best candidates for electric mobility applications.

[0003] The possible characteristics of lithium positive electrode active materials are: x Ni y Mn 2-y O 4-δ , where 0.9≤x≤1.1, 0.4≤y≤0.5 and 0≤δ≤0.1. Such materials can be used, for example, in portable devices (US 8,404,381B2); electric vehicles, energy storage systems, auxiliary power units (APUs) and uninterruptible power supplies (UPSs). Lithium cathode active materials are seen as potential successors to current lithium secondary battery cathode materials, such as LiCoO 2 , and LiMn 2 O 4 .

[0004] Lithium positive electrode active materials can be prepared from precursors obtained by a coprecipitation process. Due to the coprecipitation process, the precursor and the product are spherical. Electrochimica Acta (2014), pages 290-296 discloses a material prepared from a precursor obtained as follows: first a coprecipitation process, then sintering (heat treatment) at 500°C and then at 800°C. The obtained product is highly crystalline and has a spinel structure after the first heat treatment step (500°C). The product was observed to be uniform in morphology with a tap density of 2.03 gcm -3 , and the uniform secondary particle size is 5.6 μm. Electrochimica Acta (2004) pp. 939-948 states that uniformly distributed spherical particles have a higher tap density than irregular particles because they have greater fluidity and are easy to stack. It is speculated that the obtained layered morphology and LiNi 0.5 Mn 1.5 O 4 The larger secondary particle size increases the tap density.

[0005] Lithium positive electrode active materials can also be prepared from precursors obtained by mechanically mixing starting materials to form a homogeneous mixture, as disclosed in US 8,404,381 B2 and US 7,754,384 B2. The precursor is heated at 600°C, annealed between 700°C and 950°C, and cooled in an oxygen-containing medium. It is disclosed that a heat treatment step of 600°C is required to ensure that lithium is well incorporated into the mixed nickel and manganese oxide precursors. It is also disclosed that the annealing step is usually carried out at a temperature above 800°C to cause oxygen loss while producing the desired spinel morphology. It is further disclosed that subsequent cooling in an oxygen-containing medium can partially return oxygen. US 7,754,384B2 does not mention the tap density of the material. It is also disclosed that 1 mol% to 5 mol% excess lithium is used to prepare the precursor.

[0006] J. Electrochem. Soc. (1997) 144, pp. 205-213, also discloses the preparation of spinel LiNi from precursors. 0.5 Mn 1.5 O 4 , the precursor is prepared by mechanically mixing the starting materials to obtain a homogeneous mixture. The precursor is heated three times at 750°C in air and once at 800°C. 0.5 Mn 1.5 O 4 When heated above 650 °C, it loses oxygen and disproportionates; however, the LiNi 0.5 Mn 1.5 O 4 Stoichiometric ratios. Particle size and tap density are not disclosed. It is also disclosed that the preparation of spinel phase materials by mechanical mixing of the starting materials to obtain a homogeneous mixture is difficult and that precursors prepared by a sol-gel process are preferred.

[0007] WO2017220162 teaches an electrode material for a lithium-ion-based electrochemical cell, which comprises primary particles of a Mn-containing spinel-type metal oxide selected from spinel-type lithium-nickel-manganese oxide, spinel-type lithium-manganese oxide or a mixture thereof, wherein the Mn in the Mn-containing spinel-type metal oxide is partially substituted by a replacing element selected from Si, Hf, Zr, Fe, Al, V and a mixture thereof, and wherein the primary particles aggregate to form secondary particles, and the secondary particles have a microspherical shape.

[0008] US2018053940 relates to cathode active material particles and a secondary battery including the same, and provides cathode active material particles including: a core including a first lithium transition metal oxide; and a shell surrounding the core, wherein the shell has a form in which metal oxide particles are embedded in a second lithium transition metal oxide, and at least a part of the metal oxide particles are present by being exposed on the surface of the shell. It is disclosed that the cathode active material particles prevent side reactions between transition metals and an electrolyte by exposing a part of a metal oxide having low reactivity on the surface of the active material, thereby improving safety and lifespan. It teaches that stability can be maintained even under high temperature and battery breakdown conditions as the conductivity of the active material becomes low.

[0009] Accordingly, it is desirable to provide a cathode active material having improved cycle stability at room temperature and elevated temperatures. SUMMARY OF THE INVENTION

[0010] In one aspect, there is provided a cathode active material including:

[0011] (a) a first component including lithium transition metal oxide spinel particles selected from oxides of the formula Li x Ni y Mn 3-x-y O 4 where 0.98 < x < 1.00 and 0.41 < y < 0.50;

[0012] (b) a second oxide component selected from oxides of Sr, Y, Zr, Nb, La, and W and mixtures thereof; the total amount thereof is 0.01 atomic % to 3 atomic % based on the total number of atoms in the cathode active material, where the cathode active material is

[0013] (i) particles including one or more single crystals of the first component (a), wherein the arithmetic mean of the minimum Feret diameters of the particles measured using a scanning electron microscope is not greater than 3 μm,

[0014] where the second oxide component (b) is disposed at least partially on the surface of the particles; and / or

[0015] (ii) secondary particles including agglomerated single crystal particles of the first component (a), wherein the second oxide component (b) is dispersed at the interfaces between the single crystal particles on the surfaces of the single crystal particles, thereby throughout the secondary particles, where the average particle size (D50) of the secondary particles is less than 20 μm.

[0016] In a second aspect, there is provided a method for preparing a cathode active material including:

[0017] (a) a first component including lithium transition metal oxide spinel particles selected from oxides of the formula Lix Ni y Mn 3-x-y O 4 lithium transition metal oxide spinel particles of an oxide of, where 0.98 < x < 1.00 and 0.41 < y < 0.50;

[0018] (b) a second oxide component selected from oxides of Sr, Y, Zr, Nb, La, and W and mixtures thereof;

[0019] wherein the positive electrode active material is particles formed from one or more single crystals of the first component, and wherein the second oxide component is disposed on the surface of the particles;

[0020] The method includes the following steps:

[0021] (i) providing one or more lithium precursor compounds and one or more transition metal precursor compounds,

[0022] (ii) contacting the precursor compounds and grinding the precursor compounds to form a ground mixture;

[0023] (iii) calcining the ground mixture at a temperature of at least 800 °C to provide a calcined mixture;

[0024] where

[0025] (A) before the calcination step (iii), combining the second oxide or second oxide precursor with one or more lithium precursor compounds and one or more transition metal precursor compounds; or

[0026] (B) after the calcination step (iii), combining the calcined mixture with the second oxide.

[0027] In another aspect, a method for preparing a positive electrode active material is provided, the positive electrode active material comprising:

[0028] (a) a first component comprising lithium transition metal oxide spinel particles of an oxide selected from the formula Li x Ni y Mn 3-x-y O 4 where 0.98 < x < 1.00 and 0.41 < y < 0.50;

[0029] (b) a second oxide component selected from oxides of Sr, Y, Zr, Nb, La, and W and mixtures thereof;

[0030] where the positive electrode active material is secondary particles formed from aggregated single crystal particles of the first component, and wherein the second oxide component is dispersed at the interfaces between the single crystal particles on the surface of the single crystal particles, thereby throughout the secondary particles.

[0031] The method comprises the following steps:

[0032] (i) Providing one or more transition metal compounds,

[0033] (ii) Contacting the transition metal compound with one or more compounds of a metal containing a second oxide component or with the second oxide component,

[0034] (iii) Precipitating the transition metal and the metal of the second oxide component to form a precipitate, and washing the precipitate to form a first precursor mixture;

[0035] (iv) Contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture, and

[0036] (v) Calcining the second precursor mixture. DETAILED DESCRIPTION OF THE INVENTION

[0038] As discussed herein, in one aspect, there is provided a positive electrode active material comprising:

[0039] (a) A first component comprising lithium transition metal oxide spinel particles selected from oxides of the formula Li x Ni y Mn 3-x-y O 4 where 0.98 < x < 1.00 and 0.41 < y < 0.50;

[0040] (b) A second oxide component selected from oxides of Sr, Y, Zr, Nb, La and W and mixtures thereof; the total amount thereof is 0.01 atomic % to 3 atomic % based on the total number of atoms in the positive electrode active material, wherein the positive electrode active material is

[0041] (i) Particles comprising one or more single crystals of the first component (a), wherein the arithmetic mean of the minimum Feret diameters of the particles measured using a scanning electron microscope is not greater than 3 μm, wherein the second oxide component (b) is at least partially provided on the surface of the particles; and / or

[0042] (ii) Secondary particles comprising agglomerated single crystal particles of the first component (a), wherein the second oxide component (b) is dispersed at the interfaces between the single crystal particles on the surface of the single crystal particles, thereby throughout the secondary particles, wherein the average particle size (D50) of the secondary particles is less than 20 μm.

[0043] In the positive electrode active material of the present invention, at least two oxide components are provided. The first oxide component is a lithium transition metal oxide in particle form. The second oxide component is another material selected from oxides of Sr, Y, Zr, Nb, La and W, such as ZrO 2 The first oxide and the second oxide are configured such that the second oxide is always disposed proximate to the bulk of the lithium transition metal oxide. This is achieved by arranging the particles in one of two possible configurations. In the first configuration, the particles are formed from one or more single crystals of the first component, and the second oxide component is at least partially disposed on the surface of the particles. The particles are formed such that they are relatively small, in particular, they are formed such that the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is no greater than 3 μm.

[0044] Those skilled in the art will appreciate that the Feret's diameter is the distance between two parallel lines placed relative to each other as tangents on the particle profile. The Feret's diameter is also known as the caliper diameter because it corresponds to placing a caliper on an object and measuring a dimension along a certain direction. The minimum Feret's diameter is the smallest distance between two such tangents, or the smallest distance that can be measured by a caliper. This means that, when properly oriented, the minimum Feret's diameter corresponds to the smallest sieve size that this particular particle may pass through. For example, for a rectangular particle, the minimum Feret's diameter corresponds to the shortest side, and for a circle, the minimum Feret's diameter corresponds to the diameter of the circle.

[0045] In the second configuration, the secondary particles are formed by agglomerated single crystal particles of the first component. In these agglomerated particles, the second oxide component is not only disposed on the surface of the secondary particles, but also dispersed on the surface of the single crystal particles at the interface between the single crystal particles, thereby spreading throughout the secondary particles.

[0046] We have found that by providing these specific configurations of particles, where the second oxide is always disposed proximal to the bulk of the lithium transition metal oxide, we are able to provide cathode active materials with improved cycling stability at room temperature and / or at elevated temperatures.

[0047] For ease of reference, these and other aspects of the present invention are now discussed under the appropriate section headings. However, the teachings under each section are not necessarily limited to each particular section.

[0048] Positive electrode active material

[0049] In one aspect, the positive electrode active material comprises particles formed of one or more single crystals of the first component, wherein the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is no greater than 3 μm, wherein the second oxide component is at least partially disposed on the surface of the particles.

[0050] The Feret diameter of a particle is well understood by those skilled in the art. The Feret diameter is used to analyze particle size and its distribution and has been common in scientific literature since the 1970s. The Feret diameter is a measure of the size of an object and is defined as the distance between two parallel planes that bound the object in a direction perpendicular to it. For this reason, it is also known as the caliper diameter, referring to the measurement of the size of an object with a caliper.

[0051] The size of single crystal particles or agglomerates of single crystal particles used to determine the Feret diameter can be evaluated by scanning electron microscopy (SEM). To prepare the material for such a measurement, it is embedded in epoxy resin and polished to a flat surface so that cross-sections of the individual particles that make up the sample can be imaged. The images obtained in this way are then analyzed to measure the size and shape of the particles. The minimum Feret diameter is the minimum distance between two such tangent lines and can be considered as the smallest sieve size that this particular particle may pass through, e.g. for a rectangular particle the minimum Feret diameter corresponds to the shortest side, and for a circle the minimum Feret diameter corresponds to the diameter of the circle.

[0052] The Feret diameter of the particles can be determined according to the following method. The samples for scanning electron microscopy (SEM) were prepared by embedding the material in epoxy resin and polishing it to a flat surface. SEM images were collected on a Zeiss GeminiSEM 500 equipped with a field emission gun (FEG), using an accelerating voltage of 10 kV and an energy selective backscattering (ESB) detector, which is a backscattered electron detector type. The pixel size is 0.01 μm per pixel. A total of 25 images were collected and stitched into a high-resolution image of 4930 pixels × 3697 pixels, corresponding to an image area of ​​48 μm*36 μm. The images were analyzed according to the following procedure, and a total of 663 particles were detected and analyzed. Images were analyzed using ImageJ software (https: / / imagej.nih.gov). The procedure is as follows:

[0053] Thresholding and segmentation using the "Otsu algorithm"

[0054] Apply a binary process to "fill holes"

[0055] Apply the binary process "Erode" 8 times

[0056] Apply the binary process, “Dilate” 6 times.

[0057] Use of "analytical particles" with no size restrictions

[0058] Fill holes is used to fill possible holes inside particles. Use erosion followed by dilation steps to remove possible noise and ensure that closely laid particles are separated.

[0059] In one aspect, the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is no greater than 2.5 μm, such as no greater than 2 μm, such as no greater than 1.8 μm, such as no greater than 1.6 μm, such as no greater than 1.4 μm, such as no greater than 1.2 μm, such as no greater than 1 μm, such as no greater than 0.8 μm.

[0060] In one aspect, the particles have an arithmetic mean of minimum Feret's diameter measured using a scanning electron microscope of at least 0.1 μm, such as at least 0.2 μm, such as at least 0.3 μm, such as at least 0.4 μm, such as at least 0.5 μm, such as at least 0.6 μm, such as at least 0.7 μm.

[0061] In one aspect, the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is 0.1 μm to 2.5 μm, such as 0.1 μm to 2 μm, such as 0.1 μm to 1.8 μm, such as 0.1 μm to 1.6 μm, such as 0.1 μm to 1.4 μm, such as 0.1 μm to 1.2 μm, such as 0.1 μm to 1 μm, such as 0.1 μm to 0.8 μm.

[0062] The size of irregularly shaped particles can also be quantified with reference to the diameter of a circle of equal projected area. For particles with a projected area of ​​A, the equal-area circle therefore has a diameter d=2*√(A / (2*π)). In one aspect, the positive electrode active material includes particles formed from one or more single crystals of the first component, wherein the average equivalent circular diameter of the particles measured using a scanning electron microscope is no greater than 3 μm. In one aspect, the average equivalent circular diameter of the particles measured using a scanning electron microscope is no greater than 2.5 μm, such as no greater than 2 μm, such as no greater than 1.8 μm, such as no greater than 1.6 μm, such as no greater than 1.4 μm, such as no greater than 1.2 μm, such as no greater than 1 μm, such as no greater than 0.9 μm.

[0063] In one aspect, the particles have an average equivalent circular diameter measured using a scanning electron microscope of at least 0.1 μm, such as at least 0.2 μm, such as at least 0.3 μm, such as at least 0.4 μm, such as at least 0.5 μm, such as at least 0.6 μm, such as at least 0.7 μm.

[0064] In one aspect, the average equivalent circular diameter of the particles measured using a scanning electron microscope is 0.1 μm to 2.5 μm, such as 0.1 μm to 2 μm, such as 0.1 μm to 1.8 μm, such as 0.1 μm to 1.6 μm, such as 0.1 μm to 1.4 μm, such as 0.1 μm to 1.2 μm, such as 0.1 μm to 1 μm, such as 0.1 μm to 0.9 μm.

[0065] In one aspect, the positive electrode active material comprises secondary particles formed by agglomerated single crystal particles of the first component, wherein the second oxide component is dispersed on the surface of the single crystal particles at the interface between the single crystal particles, thereby spreading throughout the secondary particles. It will be appreciated by those skilled in the art that the second oxide component is dispersed throughout the secondary particles, not just on the surface of the secondary particles, to ensure that the second oxide component is very close to the crystals of the lithium transition metal oxide. This ensures that in use, the positive effect of the second oxide component is enhanced, and a positive electrode active material having improved cycle stability at room temperature and at elevated temperatures is provided.

[0066] The secondary particles can be of any suitable size. In one aspect, the average particle size (D50) of one or more secondary particles is less than 50 μm, such as less than 45 μm, such as less than 40 μm, such as less than 35 μm, such as less than 30 μm, such as less than 25 μm, such as less than 20 μm, such as less than 15 μm, such as less than 10 μm.

[0067] In one aspect, the average particle size (D50) of the one or more secondary particles is at least 1 μm, such as at least 2 μm, such as at least 3 μm, such as at least 4 μm, such as at least 5 μm, such as at least 10 μm.

[0068] In one aspect, the average particle size (D50) of one or more secondary particles is 4 μm to 50 μm, such as 4 μm to 45 μm, such as 4 μm to 40 μm, such as 4 μm to 35 μm, such as 4 μm to 30 μm, such as 4 μm to 25 μm, such as 4 μm to 20 μm, such as 4 μm to 15 μm, such as 4 μm to 10 μm.

[0069] One way to quantify particle size is to plot the entire particle size distribution, i.e., the volume fraction of particles of a particular size as a function of the particle size. In this distribution, D10 is defined as the particle size where 10% of the population distribution is below the D10 value, D50 is defined as the particle size where 50% of the population distribution is below the D50 value (i.e., the median), and D90 is defined as the particle size where 90% of the population distribution is below the D90 value. Common methods for determining particle size distribution include laser diffraction measurements and scanning electron microscopy measurements, combined with image analysis. The definition and measurement of the particle size distribution value D50 are described in Jillavenkatesa A, Dapkunas SJ, Lin-Sien Lum: Particle Size Characterization, NIST (National Institute of Standards and Technology) Special Publication 960-1, 2001.

[0070] As discussed herein, in one aspect, the positive electrode active material is a particle formed of one or more single crystals of a first component, wherein the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is no greater than 3 μm, wherein the second oxide component is at least partially disposed on the surface of the particles. Secondary particles formed from agglomerated single crystal particles of the first component may or may not be formed from particles having these specific properties. In other words, secondary particles formed from agglomerated single crystal particles of the first component may or may not be formed from one or more single crystals of the first component, wherein the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is no greater than 3 μm, wherein the second oxide component is at least partially disposed on the surface of the particles.

[0071] The secondary particles are formed by agglomerated single crystal particles of the first component. As discussed herein, the first component comprises lithium transition metal oxide particles. In one aspect, the single crystal particles agglomerated to form the secondary particles can be particles of different lithium transition metal oxides. In one aspect, the single crystal particles agglomerated to form the secondary particles are each single crystal particles of the same lithium transition metal oxide. In other words, in each of the single crystal particles, the first component can be the same lithium transition metal oxide.

[0072] The present invention provides a positive active material in which a large part of the surface of each single crystal is not in contact with another crystal surface. Therefore, the positive active material provides such a single crystal in which a large part of the crystal surface is a free surface. As will be understood by those skilled in the art, when a crystallized lithium transition metal oxide is prepared, single crystals of the lithium transition metal oxide grow during the preparation process, and these single crystals can contact other single crystals to form boundaries between crystals. The boundary between each crystal and another crystal is no longer the outer surface of the crystal, and the availability is low. By providing small particles having an arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope of no more than 3 μm, or providing secondary particles formed by agglomerated single crystal particles, the availability of the crystal (which has a limited number of boundaries with other crystals) is maintained. In one aspect, the positive active material is one or more particles formed by one or more single crystals of the first component, wherein at least 20% of the single crystal surface is a free surface. It will be understood by those skilled in the art that the term "free surface" refers to a surface that is not bound to another crystal. In one aspect, the positive electrode active material is one or more particles formed from one or more single crystals of the first component, wherein at least 30% of the single crystal surface is free surface, such as at least 40% of the single crystal surface is free surface, such as at least 50% of the single crystal surface is free surface, such as at least 60% of the single crystal surface is free surface, such as at least 70% of the single crystal surface is free surface, such as at least 80% of the single crystal surface is free surface.

[0073] In one embodiment, the tap density of the positive electrode active material is at least 1.5 g / cm 3 In one aspect, the tap density of the positive electrode active material is at least 1.6 g / cm 3 ; such as at least 1.7g / cm 3 , such as at least 1.8g / cm 3 .

[0074] In one embodiment, the positive electrode active material has a tap density of at least 2.0 g / cm 3 In one aspect, the tap density of the positive electrode active material is at least 2.1 g / cm 3 ; such as at least 2.2g / cm 3 , such as at least 2.3g / cm 3 , especially at least 2.4 g / cm 3 .

[0075] In one embodiment, when formed from particles formed from one or more single crystals of the first component, the positive electrode active material has a tap density of at least 1.5 g / cm 3 In one aspect, the tap density of the positive electrode active material is at least 1.6 g / cm3 ; such as at least 1.7g / cm 3 , such as at least 1.8g / cm 3 , especially at least 1.9 g / cm 3 .

[0076] "Tapped density" is a term used to describe the bulk density of a powder (or granular solid) after consolidation / pressing according to a specified number of measurements of "tapping" a container of powder, usually from a predetermined height. The method of "tapping" is best described as "lifting and dropping". In this context, tapping should not be confused with tamping, side impact or vibration. The measurement method may affect the tapped density value, so the same method should be used when comparing the tapped densities of different materials. The tapped density of the present invention is measured by weighing a graduated cylinder with an inner diameter of 10 mm before and after adding about 5g of powder to record the mass of added material, then tapping the graduated cylinder on a table for a period of time, and then reading the volume of the tapped material. Generally, tapping should be continued until further tapping does not provide any further volume change. By way of example only, tapping can be performed about 120 or 180 times in one minute.

[0077] Lithium transition metal oxides

[0078] As will be appreciated by those skilled in the art, the lithium transition metal oxide can be any suitable lithium transition metal oxide. In one aspect, the lithium transition metal oxide is a lithium nickel manganese oxide spinel.

[0079] "Spinel" refers to a lattice in which oxygen is arranged in a cubic close-packed lattice that may be slightly distorted, with cations occupying interstitial octahedral and tetrahedral sites in the lattice. Oxygen and octahedral coordinated cations form a framework structure with a three-dimensional channel system that occupies tetrahedral coordinated cations. The ratio between tetrahedral coordinated cations and octahedral coordinated cations is about 1:2, and the ratio of cations to oxygen in a spinel-type structure is about 3:4. The cations in the octahedral site can be composed of a single element or a mixture of different elements. If a mixture of different types of octahedral coordinated cations itself forms a three-dimensional periodic lattice, spinel is called an ordered spinel. If cations are more randomly distributed, spinel is called a disordered spinel. Examples of ordered spinel and disordered spinel are described in P4332 and Fd-3m space groups, respectively, and are described in Adv. Mater. (2012) 24, pp. 2109-2116.

[0080] The phase composition of lithium cathode active materials can be determined using Cu Kα radiation Determined using an X-ray diffraction pattern obtained with a Phillips PW1800 instrument system operating in Bragg-Brentano mode in θ-2θ geometry. The observed data need to be corrected for experimental parameters that cause offsets in the observed data. This is achieved using the whole-profile fundamental parameter method implemented in TOPAS software from Bruker. The phase composition determined by Rietveld analysis is given in weight percent, with a typical uncertainty of 1-2 percentage points, and represents the relative composition of all crystalline phases. Thus, any amorphous phase is not included in the phase composition.

[0081] In one aspect, the lithium transition metal oxide is selected from oxides of the formula Li x Ni y Mn 3-x-y O 4 where 0.98 < x < 1.00 and 0.41 < y < 0.50.

[0082] One embodiment of the method of the present invention relates to a lithium positive electrode active material comprising at least 95 wt% of a spinel phase Li x Ni y Mn 3-x-y O 4 ; 0.9 ≤ x ≤ 1.1, and 0.4 ≤ y ≤ 0.5.

[0083] It should be noted that the lithium positive electrode active material may contain a small amount of other elements in addition to Li, Ni, Mn, and O. Such elements may be, for example, one or more of the following: B, N, F, Mg, Al, Si, P, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Sn, W. This small amount of such elements may originate from impurities in the starting materials used to prepare the lithium positive electrode active material, or may be added as dopants for the purpose of improving certain properties of the lithium positive electrode active material.

[0084] The second oxide

[0085] As discussed herein, the second oxide component is selected from oxides of Sr, Y, Zr, Nb, La, and W and mixtures thereof. In one aspect, the second oxide component is at least an oxide of Sr. In one aspect, the second oxide component is at least an oxide of Y. In one aspect, the second oxide component is at least an oxide of Zr. In one aspect, the second oxide component is at least an oxide of Nb. In one aspect, the second oxide component is at least an oxide of La. In one aspect, the second oxide component is at least an oxide of W.

[0086] It has been found that the oxide of Zr (ZrO 2) is particularly preferred. In one aspect, based on the metal of the second oxide component, Zr is at least 90 atomic %. In one aspect, based on the metal of the second oxide component, Zr is at least 95 atomic %. In one aspect, based on the metal of the second oxide component, Zr is at least 99 atomic %. In one aspect, the second oxide component is an oxide of Zr.

[0087] When the second oxide component is or includes an oxide of Zr, the positive electrode active material can be represented by the formula zLi x Ni y Mn 3-x- y O 4 ·(1 - z)ZrO 2 where 0.98 < x < 1.00 and 0.41 < y < 0.50, and where 0.96 < z < 1.

[0088] In one aspect, based on the total number of atoms in the positive electrode active material, the second oxide component is present in an amount providing a total amount of Sr, Y, Zr, Nb, La, and W of less than 7 atomic %, such as less than 6 atomic %, such as less than 5 atomic %, such as less than 4 atomic %, such as less than 3 atomic %, such as less than 2 atomic %, such as less than 1 atomic %, such as less than 0.8 atomic %, such as less than 0.6 atomic %, such as less than 0.4 atomic %.

[0089] In one aspect, based on the total number of atoms in the positive electrode active material, the second oxide component is present in an amount providing a total amount of Sr, Y, Zr, Nb, La, and W of greater than 0.01 atomic %, such as greater than 0.02 atomic %, such as greater than 0.05 atomic %, such as greater than 0.1 atomic %, such as greater than 0.2 atomic %, such as greater than 0.5 atomic %, such as greater than 1 atomic %.

[0090] In one aspect, based on the total number of atoms in the positive electrode active material, the second oxide component is present in an amount providing a total amount of Sr, Y, Zr, Nb, La, and W of from 0.01 atomic % to 7 atomic %, such as from 0.01 atomic % to 6 atomic %, such as from 0.01 atomic % to 5 atomic %, such as from 0.01 atomic % to 4 atomic %, such as from 0.01 atomic % to 3 atomic %, such as from 0.01 atomic % to 2 atomic %, such as from 0.01 atomic % to 1 atomic %, such as from 0.01 atomic % to 0.8 atomic %, such as from 0.01 atomic % to 0.6 atomic %, such as from 0.01 atomic % to 0.4 atomic %.

[0091] In one aspect, the second oxide component is present in an amount to provide a total amount of 0.05 atomic % to 7 atomic %, such as a total amount of 0.05 atomic % to 6 atomic %, such as a total amount of 0.05 atomic % to 5 atomic %, such as a total amount of 0.05 atomic % to 4 atomic %, such as a total amount of 0.05 atomic % to 3 atomic %, such as a total amount of 0.05 atomic % to 2 atomic %, such as a total amount of 0.05 atomic % to 1 atomic %, such as a total amount of 0.05 atomic % to 0.8 atomic %, such as a total amount of 0.05 atomic % to 0.6 atomic %, such as a total amount of 0.05 atomic % to 0.4 atomic % of Sr, Y, Zr, Nb, La and W based on the total number of atoms in the positive electrode active material.

[0092] The second oxide component is provided in combination with a first component comprising lithium transition metal oxide particles. The second oxide component may be mixed with the lithium transition metal oxide. It is desired that the second oxide component is in close contact with the first component comprising the lithium transition metal oxide. In one aspect, the second oxide component is bonded to the surface of particles formed by one or more single crystals or to the surface of single crystal particles. With regard to the term "bound", it should be understood that the second oxide component is fixed to the first component comprising the lithium transition metal oxide, for example, by some symbiosis between the second oxide component and the first component comprising the lithium transition metal oxide.

[0093] As discussed herein, the second oxide component is at least partially disposed on the surface of particles formed from one or more single crystals of the first component. It should be understood that while it is desirable to provide the second oxide component on the surface of the first component crystals, some of the second oxide component may be buried between the boundaries of the first component crystals. In one aspect, at least 50%, such as at least 60%, such as at least 70%, such as at least 80%, such as at least 90%, such as at least 95%, such as at least 99%, such as at least 99.9% of the second oxide component is disposed on the surface of particles formed from one or more single crystals of the first component.

[0094] method

[0095] As can be appreciated from this description, two different approaches are provided.

[0096] The first method is for preparing particles formed of one or more single crystals of a first component, wherein a second oxide component is at least partially disposed on the surface of the particles. In this aspect, a method for preparing a positive electrode active material is provided, the positive electrode active material comprising

[0097] (a) a first component comprising a component selected from the formula Li x Ni y Mn 3-x-y O 4Lithium transition metal oxide spinel particles of the oxide, where 0.98 < x < 1.00 and 0.41 < y < 0.50;

[0098] (b) A second oxide component selected from oxides of Sr, Y, Zr, Nb, La, and W and mixtures thereof;

[0099] Wherein the positive electrode active material is particles formed from one or more single crystals of the first component, and the second oxide component is disposed on the surface of the particles.

[0100] The method includes the following steps:

[0101] (i) Providing one or more lithium precursor compounds and one or more transition metal precursor compounds,

[0102] (ii) Contacting the above precursor compounds and grinding the precursor compounds to form a ground mixture;

[0103] (iii) Calcining the ground mixture to provide a calcined mixture;

[0104] Wherein

[0105] (A) Before the calcination step (iii), combining a second oxide or a second oxide precursor with one or more lithium precursor compounds and one or more transition metal precursor compounds; or

[0106] (B) After the calcination step (iii), combining the calcined mixture with a second oxide.

[0107] In this aspect, the positive electrode active material can be particles formed from one or more single crystals of the first component, wherein the arithmetic mean of the minimum Feret diameters of the particles measured using a scanning electron microscope is not greater than 3 μm, and the second oxide component is at least partially disposed on the surface of the particles; or

[0108] The lithium precursor compound of the first method can be selected from Li 2 CO 3 , LiOH, LiNO 3 and mixtures thereof.

[0109] The transition metal precursor compound of the first method can be selected from oxides of Mn and Ni, carbonates of Mn and Ni, and hydroxides of Mn and Ni. In one aspect, the transition metal precursor compound of the first method is selected from MnO 2 , Mn 3 O 4 , MnCO 3 , NiCO 3 , basic nickel carbonate such as Ni(CO 3 )x (OH) y ·zH 2 O, and mixtures thereof, wherein 2x+y=2.

[0110] The second oxide precursor of the first method can be selected from any oxide, carbonate, hydroxide and mixtures thereof of Sr, Y, Zr, Nb, La and W. In one aspect, the second oxide precursor of the first method is selected from ZrO 2 、Zr(CO 3 ) x (OH) y , and mixtures thereof, wherein 2x+y=4.

[0111] In one aspect, the milled mixture is calcined at a temperature of at least 800° C. In an embodiment of the method, the milled mixture is calcined at a temperature of 300° C. to 1200° C., such as 400° C. to 1100° C., such as 500° C. to 1100° C., such as 500° C. to 1000° C., such as 600° C. to 1000° C., such as 700° C. to 950° C.

[0112] The ground mixture can be calcined for any suitable period of time. In one aspect, the ground mixture is calcined for a period of at least 10 minutes, such as at least 30 minutes, such as at least 1 hour, such as at least 2 hours, such as at least 3 hours. In one aspect, the ground mixture is calcined for a period of 10 minutes to 10 hours, such as 30 minutes to 10 hours, such as 1 hour to 10 hours, such as 2 hours to 10 hours, such as 3 hours to 10 hours.

[0113] After the ground mixture is calcined, it is usually cooled. "Cooling" refers to treating the material at a gradually decreasing temperature or temperature range to reduce the temperature of the material. When the temperature drops from 900° C. to 700° C., typical cooling conditions are cooling 1° C. to 5° C. per minute. Optionally, the material can be cooled to, for example, 600° C., 500° C., 400° C., 300° C., 200° C., 100° C., 50° C., room temperature (i.e., about 25° C.).

[0114] The second method is for preparing secondary particles formed of agglomerated single crystal particles of the first component, wherein the second oxide component is dispersed on the surface of the single crystal particles at the interface between the single crystal particles, thereby spreading throughout the secondary particles. A method for preparing a positive electrode active material is provided, the positive electrode active material comprising

[0115] (a) a first component comprising a component selected from the formula Li x Ni y Mn 3-x-y O 4Lithium transition metal oxide spinel particles of an oxide, where 0.98 < x < 1.00 and 0.41 < y < 0.50;

[0116] (b) A second oxide component selected from oxides of Sr, Y, Zr, Nb, La, and W and mixtures thereof;

[0117] Wherein the positive electrode active material is secondary particles formed from aggregated single crystal particles of the first component, wherein the second oxide component is dispersed at the interface between the single crystal particles on the surface of the single crystal particles, thereby throughout the secondary particles.

[0118] The method includes the following steps:

[0119] (i) Providing one or more transition metal compounds,

[0120] (ii) Contacting the transition metal compound with one or more compounds of metals containing the second oxide component or with the second oxide component,

[0121] (iii) Precipitating the metals of the transition metal and the second oxide component to form a precipitate, and washing the precipitate to form a first precursor mixture;

[0122] (iv) Contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture, and

[0123] (v) Calcining the second precursor mixture.

[0124] The lithium precursor compound can be selected from Li 2 CO 3 , LiOH, LiNO 3 and mixtures thereof.

[0125] The transition metal precursor compound of the second method can be selected from compounds of Ni and Mn that are soluble in water. In one aspect, the transition metal precursor compound is selected from MnSO 4 , Mn(NO 3 ) 2 , NiSO 4 , Ni(NO 3 ) 2 and mixtures thereof.

[0126] The second oxide precursor of the second method can be selected from any compounds of Sr, Y, Zr, Nb, La, and W and mixtures thereof. In one aspect, the second oxide precursor of the second method can be selected from any compounds of Sr, Y, Zr, Nb, La, and W, and mixtures thereof that are soluble in water. In one aspect, the second oxide precursor of the second method can be selected from Zr(SO 4 ) 2、Zr(NO 3 ) 4 and mixtures thereof.

[0127] In one aspect, the first precursor mixture is dried prior to (iv) contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture.

[0128] In one aspect, prior to (v) calcining the second precursor mixture, the second precursor mixture is dried.

[0129] In one aspect, the second precursor mixture is calcined at a temperature of at least 500°C in a nitrogen atmosphere and then calcined at a temperature of at least 800°C in air.

[0130] In an embodiment of the method, the second precursor mixture is calcined at a temperature of 300°C to 1200°C, such as 400°C to 1100°C, such as 500°C to 1100°C, such as 500°C to 1000°C, such as 600°C to 1000°C, such as 700°C to 950°C.

[0131] The second precursor mixture can be calcined for any suitable time period. In one aspect, the second precursor mixture is calcined for at least 10 minutes, such as at least 30 minutes, such as at least 1 hour, such as at least 2 hours, such as at least 3 hours, such as at least 4 hours, such as at least 5 hours, such as at least 6 hours, such as at least 7 hours, such as at least 8 hours, such as at least 9 hours, such as at least 10 hours. In one aspect, the second precursor mixture is calcined for 10 minutes to 20 hours, such as 30 minutes to 20 hours, such as at least 1 hour to 20 hours, such as at least 2 hours to 20 hours, such as at least 3 hours to 20 hours, such as at least 4 hours to 20 hours, such as at least 5 hours to 20 hours, such as at least 6 hours to 20 hours, such as at least 7 hours to 20 hours, such as at least 8 hours to 20 hours, such as at least 9 hours to 20 hours, such as at least 10 hours to 20 hours.

[0132] After the second precursor mixture is calcined, it is usually cooled. "Cooling" refers to treating the material at a gradually decreasing temperature or temperature range to reduce the temperature of the material. When the temperature drops from 900° C. to 700° C., typical cooling conditions are cooling 1° C. to 5° C. per minute. Optionally, the material can be cooled to, for example, 600° C., 500° C., 400° C., 300° C., 200° C., 100° C., 50° C., room temperature (i.e., about 25° C.).

[0133] In one embodiment, the precursor of the lithium positive electrode active material is made of two or more starting materials, wherein the starting materials have been partially or completely decomposed by heat treatment. Such starting materials are, for example, nickel-manganese carbonate and lithium carbonate, or nickel-manganese carbonate and lithium hydroxide, or nickel-manganese hydroxide and lithium hydroxide, or nickel-manganese hydroxide and lithium carbonate, or manganese oxide, nickel carbonate and lithium carbonate.

[0134] In one embodiment, the starting material further comprises up to 2 mol% of other elements besides Li, Ni, Mn and O. These elements may be, for example, one or more of the following: B, N, F, Mg, Al, Si, P, S, Ca, Ti, Cr, Fe, Co, Cu, Zn, Zr, Sn, W, any mixture thereof or any chemical composition containing one or more of these compounds. Dopants may originate from additives or impurities in the starting material.

[0135] "Precursor" refers to a composition prepared by mechanically mixing or co-precipitating starting materials to obtain a homogeneous mixture (Journal of Power Sources (2013) 238, 245-250); mixing a lithium source with a composition prepared by mechanically mixing starting materials to obtain a homogeneous mixture (Journal of Power Sources (2013) 238, 245-250); or mixing a lithium source with a composition prepared by co-precipitation of starting materials (Electrochimica Acta (2014) 115, 290-296).

[0136] The starting material is selected from one or more compounds selected from metal oxides, metal carbonates, metal oxalates, metal acetates, metal nitrates, metal sulfates, metal hydroxides and pure metals; wherein the metal is selected from nickel (Ni), manganese (Mn) and lithium (Li) and mixtures thereof. Preferably, the starting material is selected from one or more compounds selected from manganese oxide, nickel oxide, manganese carbonate, nickel carbonate, manganese sulfate, nickel sulfate, manganese nitrate, nickel nitrate, lithium hydroxide, lithium carbonate and mixtures thereof. The metal oxidation state of the starting material may be different; for example, MnO, Mn 3 O 4 , Mn 2 O 3 、MnO 2 、Mn(OH)、MnOOH、Ni(OH) 2 ,NiOOH.

[0137] In one embodiment, a reducing atmosphere is created in a portion of the calcination of the starting material and / or precursor material by adding a substance to the precursor composition, by decomposing the precursor, or by adding a gaseous composition to the atmosphere to remove all or part of any oxidizing species present in the atmosphere. Preferably, no ambient air can enter the reaction vessel.

[0138] "Reducing atmosphere" refers to an atmosphere that causes the thermodynamic equilibrium of the solid to shift to a phase distribution in which the average oxidation state of the metal is lower than the spinel phase at the relevant heat treatment temperature. The reducing atmosphere can be provided by the type of gas present in the reaction vessel during heating. This gas can be provided by the presence of a reducing gas; for example, the reducing gas can be one or more selected from the following: hydrogen; carbon monoxide; carbon dioxide; nitrogen; an inert gas (containing less than 15 vol% oxygen); and mixtures thereof. The term "inert gas (containing less than 15 vol% oxygen)" refers to a range covering from 0 vol% oxygen (corresponding to an inert gas without oxygen) to up to 15 vol% oxygen in the inert gas. Preferably, the amount of oxygen in the reducing atmosphere is low, for example, less than 1000 ppm, and most preferably less than 10 ppm. Typically, oxygen is not added to the atmosphere; however, oxygen may be formed during the heating process.

[0139] "Inert gas" refers to a gas that does not participate in the process. Examples of inert gases include one or more gases selected from argon; nitrogen; helium; and mixtures thereof.

[0140] Furthermore, the term "reducing atmosphere" is meant to include a composition comprising two or more gases, one of which is considered a non-reducing atmosphere gas when used independently of the other gases, and a second gas or substance reduces the oxidation potential of the gas mixture. The total reducing power of the atmosphere corresponds to a reducing atmosphere. Such a composition may be selected from the group consisting of: nitrogen, an inert gas with less than 15 vol% oxygen, air, and hydrogen; air and CO; air and methanol; air and carbon dioxide.

[0141] In addition, a "reducing atmosphere" can be obtained by adding a substance to the precursor composition or by adding a gaseous composition to the atmosphere to remove all or part of any oxidizing substances present in the atmosphere of the reaction vessel during heating. The substance can be added to the precursor during the preparation of the precursor or before the heat treatment. The substance can be any oxidizable material, preferably comprising carbon, for example, the substance can be one or more compounds selected from graphite, acetic acid, carbon black, oxalic acid, wood fiber and plastic material.

[0142] "Calcination" means treating a material at a temperature or temperature range to obtain a desired degree of crystallinity. The temperature or temperature range is intended to indicate the temperature of the material being heat treated. Typical calcination temperatures are about 500°C, about 600°C, about 700°C, about 800°C, about 900°C, about 1000°C, and temperatures range from about 300°C to about 1200°C; about 500°C to about 1000°C; 650°C to 950°C. The term "calcined at a temperature between X°C and Y°C" is not meant to be limited to one specific temperature between X and Y; rather, the term also includes calcination to a temperature range within X to Y during heating.

[0143] The method of the present invention may include one or more other steps. These one or more other steps may be performed before, after or in between the steps listed herein.

[0144] BRIEF DESCRIPTION OF THE DRAWINGS

[0145] Embodiments of the present invention are explained by way of example and with reference to the accompanying drawings. The accompanying drawings show only examples of embodiments of the present invention and therefore they are not to be considered limiting of its scope as the invention may admit to other alternative embodiments.

[0146] Figure 1 The 1 wt% ZrO prepared as described in Example 1 is shown. 2 SEM image of LNMO.

[0147] Figure 2 A SEM image of LNMO synthesized as described in Example 2 is shown.

[0148] Figure 3 The 1 wt% ZrO prepared as described in Example 3 is shown. 2 SEM image of LNMO.

[0149] Figure 4 The 1 wt% ZrO prepared as described in Example 3 is shown. 2 Cross-sectional SEM image of LNMO.

[0150] Figure 5 The 1 wt% ZrO prepared as described in Example 4 is shown. 2 SEM image of LNMO.

[0151] Figure 6 The 1 wt% ZrO prepared as described in Example 4 is shown. 2 Cross-sectional SEM image of LNMO.

[0152] Figure 7 The 1 wt% ZrO prepared as described in Example 5 is shown. 2SEM image of LNMO. ZrO 2 Touching the surface but not in close contact.

[0153] Figure 8 The 1 wt% ZrO prepared as described in Example 6 is shown. 2 SEM image of LNMO. ZrO 2 Wetting the surface, and LNMO and ZrO 2 Close contact between.

[0154] Fig. 9 The 1 wt% ZrO prepared as described in Example 1 is shown. 2 Cross-sectional SEM image of LNMO.

[0155] Fig.10 LNMO and 1wt% ZrO 2 Electrochemical cycling of LNMO in a lithium half-cell.

[0156] Fig.11 The results show that the LNMO and 1wt% ZrO 2 Electrochemical cycling of a graphite full cell with LNMO as cathode. The test was performed at 23 °C.

[0157] Fig.12 The results show that the LNMO and 1wt% ZrO 2 Electrochemical cycling of a graphite full cell with LNMO as cathode. The test was performed at 45 °C.

[0158] The invention will now be described with reference to the following non-limiting examples. Example

[0159] Hereinafter, exemplary and non-limiting embodiments of the present invention are described in the form of experimental data. Examples 1-6 relate to methods for preparing lithium positive electrode active materials. Example 7 describes a method for measuring the minimum Feret diameter. Example 8 describes an electrochemical testing method.

[0160] Example 1 Synthesis of Lithium Cathode Active Material

[0161] Weighing MnO 2 (280 g corresponds to 3.2 mol of Mn), basic Ni(OH) x (CO 3 ) y (133 g corresponds to 0.9 mol Ni), Li 2 CO 3 (76.8 g corresponds to 2.1 mol of Li) and ZrO 2(4 g corresponds to 0.03 mol of Zr) and was ball milled as a water-based slurry in a planetary ball mill (600 rpm, counter-rotation for 30 minutes) to form a slurry with a molar ratio of Li:Ni:Mn:Zr=1.00:0.45:1.55:0.015. The mixture was then dried at 120°C for 12 hours. The powders were then mixed in a mortar for 15 minutes to obtain a precursor. The precursor was heated at 900°C for 3 hours in a 50 mL crucible and then cooled to room temperature at 1°C / min. The product was decomposed in a mortar for 15 minutes and passed through a 45 micron sieve to obtain a slurry consisting of LNMO and 1 wt% ZrO 2 Lithium positive electrode active material. Figure 1 The SEM images of the samples are shown in FIG. Figure 1 It can be seen that ZrO 2 As particles are located on the surface of LNMO particles, they appear as bright spots. 2 The coverage of LNMO by particles is as low as a few percentage points, at least less than 15%.

[0162] Example 2 Synthesis of Lithium Cathode Active Material

[0163] Weighing MnO 2 (280 g corresponds to 3.2 mol of Mn), basic Ni(OH) x (CO 3 ) y (133 g corresponds to 0.9 mol Ni) and Li 2 CO 3 (76.8 g corresponds to 2.1 mol of Li) and was ball-milled as a water-based slurry in a planetary ball mill (600 rpm, counter-rotation for 30 minutes) to form a slurry with a molar ratio of Li:Ni:Mn=1.00:0.45:1.55. The mixture was then dried at 120°C for 12 hours. The powders were then mixed in a mortar for 15 minutes to obtain a precursor. The precursor was heated at 900°C for 3 hours in a 50 mL crucible and then cooled to room temperature at 1°C / min. The product was decomposed in a mortar for 15 minutes and passed through a 45 micron sieve to obtain a lithium cathode active material consisting of LNMO. Figure 2 The SEM images of the samples are shown in .

[0164] Example 3 Synthesis of Lithium Cathode Active Material

[0165] By mixing 1M NiSO corresponding to a molar ratio of Ni:Mn:Zr = 0.45:1.55:0.015 4 、MnSO 4 and ZrSO 4 The mixture was stirred with 1 M Na 2 CO3 The solutions are combined to form spherical particles of co-precipitated Ni, Mn, Zr carbonates, which are washed and dried to remove Na + and SO 4 2- ions to co-precipitate Ni, Mn, Zr carbonate. 949 g of the co-precipitated Ni, Mn, Zr carbonate particles were mixed with 150 g of Li 2 CO 3 (corresponding to Li:Ni:Mn:Zr=1.00:0.45:1.55:0.015) and ethanol to form a viscous slurry. The slurry was shaken in a paint shaker for 3 minutes to obtain complete deagglomeration and mixing of the particulate material. The slurry was poured into a tray and dried at 80°C. The dried material was further deagglomerated by shaking in a paint shaker for 1 minute to obtain a free-flowing uniform powder mixture. The powder mixture was heated to 550°C in a furnace with a nitrogen flow rate of 2.5°C / min. The powder was heated at 550°C for 4 hours. Thereafter, the powder was treated in air at 550°C for 9 hours. The temperature was increased to 950°C with a ramp of 2.5°C / min. The temperature of 950°C was maintained for 10 hours and decreased to room temperature with a ramp of 2.5°C / min.

[0166] The powder was deagglomerated again by shaking in a paint shaker for 6 min and passed through a 45 μm sieve to obtain a 300 μm slurry consisting of LNMO and 1 wt% ZrO 2 Lithium positive electrode active material. Figure 3 and Figure 4 The SEM images of the samples are shown in FIG. Figure 3 and Figure 4 It can be seen that ZrO 2 As particles, they are located on the surface of LNMO particles, and as bright spots, they are located at the crystal boundaries of individual crystal domains in LNMO particles. 2 The coverage of LNMO by particles is as low as a few percentage points, at least less than 15%.

[0167] Example 4 Synthesis of Lithium Cathode Active Material

[0168] By mixing 1M NiSO corresponding to a molar ratio of Ni:Mn=0.45:1.55 4 and MnSO 4 The mixture was stirred with 1 M Na 2 CO 3 The solutions are combined to form spherical particles of co-precipitated Ni, Mn carbonate, which are washed and dried to remove Na + and SO 4 2-940 g of the coprecipitated Ni, Mn carbonate particles were mixed with 150 g of Li 2 CO 3 (corresponding to Li:Ni:Mn=1.00:0.45:1.55) and ethanol to form a viscous slurry. The slurry was shaken in a paint shaker for 3 minutes to obtain complete deagglomeration and mixing of the particulate material. The slurry was poured into a tray and dried at 80°C. The dried material was further deagglomerated by shaking in a paint shaker for 1 minute to obtain a free-flowing uniform powder mixture. The powder mixture was heated to 550°C in a furnace with a nitrogen flow rate of 2.5°C / min. The powder was heated at 550°C for 4 hours. Thereafter, the powder was treated in air at 550°C for 9 hours. The temperature was increased to 950°C with a ramp of 2.5°C / min. The temperature was maintained at 950°C for 10 hours and decreased to room temperature with a ramp of 2.5°C / min.

[0169] The powder was deagglomerated again by shaking in a paint shaker for 6 minutes and passed through a 45 micron sieve to obtain a lithium positive electrode active material composed of LNMO. Figure 5 and Figure 6 The SEM images of the samples are shown in .

[0170] Example 5: Synthesis of Lithium Cathode Active Material

[0171] The LNMO single crystal material from Example 2 was mixed with ZrO 2 The particles were mixed in a molar ratio corresponding to LNMO:Zr=1:0.015, and the mixture was shaken in a paint shaker for 10 minutes to allow ZrO 2 Agglomerates of primary particles disintegrate and distribute ZrO 2 Particles. Figure 7 The SEM images of the samples are shown in .

[0172] Example 6: Synthesis of Lithium Cathode Active Material

[0173] The LNMO ZrO from Example 5 was calcined as described in Examples 1 and 2. 2 mixture to obtain LNMO and ZrO 2 Closer contact between them. Figure 8 The SEM images of the samples are shown in .

[0174] Example 7: Material Characterization

[0175] The material of Example 1 was embedded in epoxy resin and polished to a flat surface. SEM images were collected on a Zeiss GeminiSEM 500 equipped with a field emission gun (FEG), using an accelerating voltage of 10 kV and an energy selective backscatter (ESB) detector, which is a backscattered electron detector type. The pixel size is 0.01 μm per pixel. A total of 25 images were collected and stitched into a high-resolution image of 4930 pixels × 3697 pixels, corresponding to an image area of ​​48 μm*36 μm. The image is shown in Fig. 9 The images were analyzed according to the following procedure, and a total of 663 particles were detected and analyzed.

[0176] Images were analyzed using ImageJ software (https: / / imagej.nih.gov). The procedure was as follows:

[0177] Thresholding and segmentation using the "Otsu algorithm"

[0178] Apply binary process "fill holes"

[0179] Apply the binary process "Erode" 8 times

[0180] Apply the binary process "Dilate" 6 times.

[0181] Use of "analytical particles" with no size restrictions

[0182] Fill holes is used to fill possible holes inside particles. Use erosion followed by dilation steps to remove possible noise and ensure that closely laid particles are separated.

[0183] Dimensional measurements:

[0184] Average minimum Feret 0.66μm

[0185] Average equivalent circle diameter 0.84 μm

[0186] Number of particles: 663

[0187] Example 8 Electrochemical Characterization

[0188] 2032 type button cells were electrochemically tested using thin composite positive and negative electrodes of metallic lithium (half-cell) and graphite composite electrodes (full cell). The thin composite positive electrode was prepared by thoroughly mixing 92 wt% of lithium positive active material (prepared according to Examples 1-4) with 4 wt% of super C65 carbon black (Timcal) and 4 wt% of PVdF binder (polyvinylidene fluoride, Sigma Aldrich) in NMP (N-methylpyrrolidone) to form a slurry. The LNMO material tested was the ZrO-containing LNMO material from Example 3.2 LNMO( Fig.10 "Containing 1wt% ZrO 2 ') and LNMO from Example 4 ( Fig.10 ), and the 40:60 ratio of LNMO and ZrO from Examples 1 and 3 2 A mixture of Figure 11-12 "Containing 1wt% ZrO 2 of LNMO") and the 40:60 LNMO mixture from Examples 2 and 4 ( Figure 11-12 in the 'LNMO').

[0189] The slurry was spread on a carbon-coated aluminum foil using a doctor blade with a gap of 100-200 μm and dried at 80° C. for 12 hours to form a film. Electrodes with a diameter of 14 mm and a load of about 12 mg of lithium positive active material were cut from the dried film, pressed in a hydraulic pelletizer (20 mm in diameter; 3 metric tons), and vacuum dried at 120° C. for 10 hours in an argon-filled glove box.

[0190] Graphite electrodes were prepared using 97wt% graphite (Imerys GDHR 15-4), 1wt% Super C65 carbon black, 1wt% CMC binder and 1wt% SBR binder in a water-based slurry. The slurry was cast on carbon-coated copper foil with a coating rod height of 30-80μm to obtain the desired loading.

[0191] In the case of half-cells, the coin cells were placed in an argon-filled glove box (<1 ppm O 2 and H 2 O), using a glass fiber separator containing 1 mol of LiPF 6 The electrolyte was prepared in EC:DEC (1:1 weight ratio) and two 250 μm thick lithium disks were used as anodes, and in the case of full cells, a Celgard H2010 separator containing 1 mol of LiPF 6 The electrolyte was assembled with 1 wt% LiBOB and 1 wt% tris(trimethylsilyl) phosphite in EC:DEC (weight ratio 1:1) and a graphite electrode with a diameter of 16 mm and a loading corresponding to an equilibrium N / P of 1.2 (in the cathode region).

[0192] Electrochemical lithium insertion and extraction were monitored using an automated cycle data logging system (Maccor) operating in galvanostatic mode.

[0193] Electrochemical testing includes half-cell ( Fig.10) 6 formation cycles (3 cycles 0.2C / 0.2C (charge / discharge) and 3 cycles 0.5C / 0.2C), 25 power test cycles (5 cycles 0.5C / 0.5C, 5 cycles 0.5C / 1C, 5 cycles 0.5C / 2C, 5 cycles 0.5C / 5C, 5 cycles 0.5C / 10C), and then 120 cycles of 0.5C / 1C to measure decay. Electrochemical testing of full cells ( Figure 11-12 ) includes 2 formation cycles at 0.1C / 0.1C, then 1 cycle at 0.1C / 0.1C with constant voltage steps during charging to 0.03C, then 49 cycles at 0.5C / 1C with constant voltage steps during charging to 0.1C. The last 1+49 cycles are then repeated multiple times to test the development of discharge capacity for a greater number of cycles. Based on 147mAhg -1 The C rate is calculated based on the theoretical specific capacity of the lithium cathode active material; therefore, for example, 0.2C corresponds to 29.6 mAg -1 20, and 10C corresponds to 1.47Ag -1 . Figure 10-11 The tests shown in are measured at 23°C, and Fig.12 The tests shown in were measured at 45°C.

[0194] Various modifications and variations of the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been described in conjunction with specific preferred embodiments, it should be understood that the claimed invention should not be overly limited to such specific embodiments. In fact, it is apparent to those skilled in the art of chemistry or related fields that various modifications of the described modes for implementing the present invention are intended to be within the scope of the following claims.

[0195] From these electrochemical measurements, it can be seen that by adding ZrO 2 The electrochemical performance, especially the capacity and cycle life, of the particles have been significantly improved.

Claims

1. A positive electrode active material comprising: (a) The first component, the first component comprising lithium transition metal oxide spinel particles comprising an oxide selected from the group consisting of Li x Ni y Mn 3-x-y O4, where 0.98 < x < 1.00 and 0.41 < y < 0.50; (b) a second oxide component selected from oxides of Sr, Y, Zr, Nb, La and W and mixtures thereof; the total amount thereof is 0.01 atomic % to 3 atomic %, based on the total number of atoms in the positive electrode active material. The positive electrode active material is (i) particles comprising one or more single crystals of the first component (a), wherein the arithmetic mean of the minimum Feret diameter of the particles measured using a scanning electron microscope is not greater than 3 μm, wherein the second oxide component (b) is at least partially disposed on the surface of the particles; and / or (ii) secondary particles comprising agglomerated single crystal particles of the first component (a), wherein the second oxide component (b) is dispersed on the surface of the single crystal particles at the interface between the single crystal particles, thereby spreading throughout the secondary particles, wherein the average particle size (D50) of the secondary particles is less than 20 μm. 2 . The positive electrode active material according to claim 1 , wherein the second oxide component (b) is at least an oxide of Zr.

3. The positive electrode active material according to claim 1 or 2, wherein the tap density of the secondary particles (ii) is at least 1.5 g / cm 3 .

4. The cathode active material according to any one of claims 1 to 3, wherein the second oxide component is present in an amount to provide a total amount of Sr, Y, Zr, Nb, La and W of 0.05 atomic % to 0.4 atomic % based on the total number of atoms in the cathode active material. 5 . The positive electrode active material according to claim 1 , wherein the second oxide component is bonded to the surface of particles formed of one or more single crystals, or to the surface of single crystal particles.

6. The positive electrode active material according to any one of claims 1 to 5, wherein the positive electrode active material is zLi x Ni y Mn 3-x-y O4·(1-z)ZrO2, where 0.98 < x < 1.00 and 0.41 < y < 0.50, and where 0.96 < z < 1.

7. The positive electrode active material according to any one of claims 1 to 6, wherein when the positive electrode active material is one or more particles of one or more single crystals comprising a first component, at least 20% of the surface of the single crystal is a free surface, preferably at least 50% of the surface of the single crystal is a free surface.

8. A method for preparing a positive electrode active material as claimed in claims 1 to 7, wherein the positive electrode active material comprises: (a) The first component, the first component comprising lithium transition metal oxide spinel particles comprising an oxide selected from the formula Li x Ni y Mn 3-x-y O4, where 0.98 < x < 1.00 and 0.41 < y < 0.50; (b) a second oxide component selected from the group consisting of oxides of Sr, Y, Zr, Nb, La and W, and mixtures thereof, wherein the positive electrode active material is a particle comprising one or more single crystals of the first component, wherein the second oxide component (b) is disposed on the surface of the particle; The method for preparing the first component (a) comprises the following steps: (i) providing one or more lithium precursor compounds and one or more transition metal precursor compounds, (ii) contacting and milling the precursor compounds to form a milled mixture; (iii) calcining the milled mixture at a temperature of at least 800° C. to provide a calcined mixture; in (A) combining a second oxide or a second oxide precursor with the one or more lithium precursor compounds and the one or more transition metal precursor compounds prior to the calcining step (iii); or (B) After the calcining step (iii), combining the calcined mixture with the second oxide.

9. The method according to claim 8, wherein the lithium precursor compound is selected from the group consisting of Li2CO3, LiOH, LiNO3 and mixtures thereof.

10. The method according to any one of claims 8 or 9, wherein the transition metal precursor compound is selected from MnO2, Mn3O4, MnCO3, NiCO3, basic nickel carbonate such as Ni(CO3) x (OH) y ·zH2O; and mixtures thereof, wherein 2x+y=2.

11. The method according to any one of claims 8 to 10, wherein the second oxide precursor is selected from ZrO2, Zr(CO3)4 and mixtures thereof.

12. A method for preparing a positive electrode active material as claimed in claims 1 to 7, wherein the positive electrode active material comprises (a) The first component, the first component comprising lithium transition metal oxide spinel particles comprising an oxide selected from the formula Li x Ni y Mn 3-x-y O4, where 0.98 < x < 1.00 and 0.41 < y < 0.50; (b) a second oxide component selected from the group consisting of oxides of Sr, Y, Zr, Nb, La and W, and mixtures thereof; wherein the positive electrode active material is a secondary particle comprising agglomerated single crystal particles of the first component, wherein the second oxide component is dispersed on the surface of the single crystal particles at the interface between the single crystal particles, thereby spreading throughout the secondary particle; The method comprises the following steps: (i) providing one or more transition metal compounds, (ii) contacting the transition metal compound with one or more compounds containing the metal of the second oxide component or with the second oxide component, (iii) precipitating a transition metal and a metal of the second oxide component to form a precipitate, and washing the precipitate to form a first precursor mixture; (iv) contacting the first precursor mixture with one or more lithium precursor compounds to form a second precursor mixture, and (v) calcining the second precursor mixture.

13. The method of claim 12, wherein the lithium precursor compound is selected from the group consisting of Li2CO3, LiOH, LiNO3, and mixtures thereof.

14. The method according to any one of claims 12 or 13, wherein the transition metal precursor compound is selected from MnSO4, Mn(NO3)2, NiSO4, Ni(NO3)2, and mixtures thereof.

15. The method according to any one of claims 12 to 14, wherein the transition metal compound used to prepare the second oxide particles is selected from Zr(SO4)2, Zr(NO3)4, and mixtures thereof.

16. The method of any one of claims 12 to 15, wherein the second precursor mixture is dried prior to (v) calcining the second precursor mixture.

17. The method according to any one of claims 12 to 16, wherein the second precursor mixture is calcined at a temperature of at least 500°C in a nitrogen atmosphere and then calcined at a temperature of at least 800°C in air.

Citation Information

Patent Citations

  • Positive electrode active material particles and secondary battery including same

    US20180053940A1

  • High-voltage positive electrode material having a spinel structure based on nickel and manganese for lithium cell batteries

    US7754384B2

  • Optimised positive electrode material for lithium cell batteries, method for the production thereof, electrode, and battery for implementing said method

    US8404381B2

  • Electrode material, use of an electrode material for a lithium-ion-based electrochemical cell, lithium-ion-based electrochemical cell

    WO2017220162A1